Fourth generation head fracture in ceramic-on-polyethylene bearing after hip revision surgery: a case report - Valentini, Roberto; Vacchiano, Andrea; Sandri, Andrea; Regis, Dario; Dall’Oca, Carlo; Magnan, Bruno (Acta Biomedica Atenei Parmensis, 2020)
Fourth generation ceramic bearings (BIOLOX delta, CeramTec AG; Phlochingen, Germany) were developed to reduce wear debris and improve fracture resistance. A case of a fourth generation head fracture in ceramic-on-polyethylene (COP) coupling after hip revision surgery is reported. A 58-year-old man was admitted to our department for increasing hip pain following a direct trauma which occurred during skiing activity 4 months before. Six years earlier, he had undergone a right cementless revision surgery with a 36-mm BIOLOX delta femoral head on polyethylene liner for metallosis and foreign body reaction after primary total hip replacement for hip osteoarthritis. At admission, radiological evaluation revealed a fracture of ceramic femoral head requiring a new revision surgery. Extensive synovectomy, lavage and capsulectomy were performed. Both acetabular cup and femoral stem were well fixed with no damage of trunnion, and therefore they were retained. A 36-mm internal diameter polyethylene acetabular liner was inserted along a 36-mm BIOLOX delta head with a BioBall adapter XL. The postoperative course was uncomplicated. At 1-year follow-up, the patient had a complete functional recovery. To our knowledge, BIOLOX delta ceramic femoral head fracture after COP hip revision surgery has not been previously reported.